2018
DOI: 10.1111/bjd.17259
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of alexithymia with effective treatment of moderate‐to‐severe psoriasis: longitudinal data from EPIDEPSO

Abstract: What's already known about this topic?• Alexithymia, the inability to identify and express emotions, is highly prevalent in patients with psoriasis.• Patients with alexithymia have a high disease burden, with impaired quality of life, anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Moreover, alexi-thymia was recognized as contributor to the development of somatization, interpersonal sensitivity, anxiety, and phobic anxiety in psoriasis patients [13]. However, it is considered a stable personality trait that, unlike anxiety and depression, should not change over time, but a reversion with therapeutic interventions has been reported, suggesting that alexithymia might be partly modifiable [28,29]. The current hypothesis is that a dimension of alexithymia, "trait alexithymia," constitutes a psychological trait that does not change over time, while another dimension, "state alexithymia," may vary based on psychological status or by therapeutic intervention impacting on patients' quality of life and, more in general, on well-being [22,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alexi-thymia was recognized as contributor to the development of somatization, interpersonal sensitivity, anxiety, and phobic anxiety in psoriasis patients [13]. However, it is considered a stable personality trait that, unlike anxiety and depression, should not change over time, but a reversion with therapeutic interventions has been reported, suggesting that alexithymia might be partly modifiable [28,29]. The current hypothesis is that a dimension of alexithymia, "trait alexithymia," constitutes a psychological trait that does not change over time, while another dimension, "state alexithymia," may vary based on psychological status or by therapeutic intervention impacting on patients' quality of life and, more in general, on well-being [22,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Bahmer and colleagues found that patients with psoriasis and atopic eczema differed regarding personality and character traits, with patients with psoriasis being less ambitious and narcissistic and patients with atopic eczema being less self-critical than the population average. 22 In addition, psoriasis has been linked to alexithymia, 46,47 which involves difficulties in recognizing and describing emotions. Such psychometric differences might lead to different ways of perceiving and coping with the respective skin disease, 48 which could explain the different effects of disease severity on PA.…”
Section: The Role Of Dermatologic Disease Severitymentioning
confidence: 99%
“…With the next-generation biologics, IL-23 and IL-17 inhibitors, 90% PASI reductions and even full clearance of disease are realistic goals. While this disease lacks a long-term structural damage component found in the other indications of TNF blockade, it is associated with compromised psychosocial status, which the evidence suggests might be limited or even reversed with successful treatment 256. Treatment guidelines now reflect tight-control and treat-to-target approaches with use of TNF inhibitors and other biologics recommended if phototherapy and conventional systemic agents fail to provide an adequate response 241.…”
Section: Changes In Treatment Paradigms Due To the Advent Of Tnf Blocmentioning
confidence: 99%